Penerapan nilai toleransi antar budaya dalam pelaksanaan hukum kewarisan Islam pada masyarakat perbatasan di Rao Pasaman Sumatera Barat - Nofiardi Nofiardi; Syafwan Rozi (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2017)
The Rao community on the border of West Sumatra inhabited by ethnic Minangkabau and ethnicMandailing is a plural society that embraces two kinship systems. The patrilineal, the matrilineal, and theparent. But in the process of their interaction for decades there has been interaction through culturaltolerance in the kinship system. Here the birth of a parental kinship and familial system is the mostdominant character in this multi ethnic Rao region as a new kinship system built in their social interactionprocess for hundreds of years. This system also affects the inheritance division system in theirinteractions. As for the inheritance distribution system, indigenous peoples of the border, especially theRao area, have applied several types of inheritance distribution: First, Rao customary people use the newcustomary law of parental system which combines two customs as the first spear in determininginheritance. Second, they use Islamic law, because the Minangkabau and Mandailing are Moslems, so theyuse Islamic law in the inheritance. Third, they use national law, because if customary law and Islamic lawdo not want to be used then they use national law. These three systems are all intercultural toleranceamid differences in their customary system between Minangkabau adat matrineal system and Mandailingcustom patrineal system.